Additive effect involving a new locus of benomyl resistance in Aspergillus nidulans - N. M. Martinez-Rossi; J. L. Azevedo (Fungal Genetics Reports, 1989)
Most of the fungicides based on the benzimidazole nucleus, including benomyl, thiabendazole and thiophanate, are systemic and because they control many important fungal diseases.